Towards an in-depth experimental and theoretical understanding of the cadmium uptake mechanism on a synthesized chitin biopolymer (2023)
This work analyzes the adsorption of cadmium, a potentially toxic pollutant, on biopolymers synthesized from shrimp shells, as a promising new adsorbent. Spectroscopic analysis, such as FTIR, ATD/ATG, XRD, and SEM/EDX techniques, were used to characterize chitin before it was exposed to cadmium ions. Experimental data indicate that Cd(II) adsorption proceeds with pseudo-second-order model kinetics and is influenced by increasing temperature. In the equilibrium, the maximum adsorption capacity obtained was 58.82 mg g−1 at a temperature of 308 K. Experiments to obtain adsorption data were performed at T = 298–318 K. The saturated adsorption capacities of Cd(II) range from 57.40 to 59.90 mg g−1. The application of the physics-statistics model indicates that the Cd(II) atoms are adsorbed on the surface of the chitosan forming a monolayer. In addition to that, the results also show that the adsorption affinity increases with the system temperature, resulting in higher affinity and an increase of 30% in the adsorption capacity. The adsorption energy was found to be around 2.5 kJ mol−1, indicating that the adsorption is physical and endothermic. The entropy was found to quickly increases (reaching a maximum value of 6 × 10−22 kJ mol−1 K−1) at low concentrations followed by the equilibrium after the 40 mg L−1, indicating that the equilibrium is quickly reached. The Gibbs free energy indicates that the process is spontaneous (ranging from −1.364 to −1.451 kJ mol−1) and that the energy tends to remain constant after 15 mg L−1. Last, the results indicate that the Cd(II) is adsorbed due to dipole–dipole interactions and possible coordination bounds. The results of tests on the adsorption of cadmium by chitin showed that this biopolymer could replace other more expensive adsorbents.